Roman lead slingshots (glandes plumbeae) in Slovenia - Laharnar, Boštjan (Arheološki vestnik, 2011)
The article deals with Roman lead slingshots from the territory of Slovenia. We present conclusions regarding their shape, method of manufacture and distribution. Analysis of several assemblages from Slovenian sites indicates Roman military activities (engagements, military stores, outposts) during different periods of the Roman conquest.